Editorial for the CHB special issue on MMOGs - Christou, Georgios; Law, Effie Lai-Chong; Geerts, David; Nacke, Lennart; Zaphiris, Panayiotis (My University, 2015)
Sociability, social structures, and the way that these are translated in the digital world are becoming an interesting topic for video game researchers (Christou, Zaphiris, Ang, & Law, 2011). Particularly, the way that these structures are manifested in Massively Multiplayer Online Games (MMOGs) becomes of interest, and that is evident from the articles in this special issue. MMOGs have become more popular than emails, according to a study by Nielsen Online (Nielsen Wire, 2010). Social cultural studies on computer games are gaining much popularity recently due to the emergence of MMOGs in which player–player interaction plays a very important role. Research in this area ranges from virtual identity, sociability design, cultural impacts of games, participatory culture as well as media and communication. The draw to these games is that they offer a new kind of “third-place” (Oldenburg, 1989), a place where people can go and socially interact, which cannot be classified as home or work.
Keywords: Sociability; Social structures; Digital world